The Role of University Public Relations in the Presence of Foreign Students in Indonesia: 2011–2021 Literature Study - Marieti Debyora Gardiana; Andre Noevi Rahmanto; Ferdian Ahya Al Putra (BIRCU, 2023)
One of the higher education ranking indicators is the ratio of international students. Therefore, universities need to formulate strategic efforts to attract international students, in which public relations plays a major role. This research was conducted with the aim of knowing research trends on the role of university public relations on foreign students in Indonesia. A qualitative study was conducted using a literature study based on the Publish or Perish program. The results of a search for publications on Google Scholar with a period of 2011–2021 were then processed using the Vos Viewer program to create data visualizations that could elaborate on the development of research trends related to this topic. The 76 most relevant terms were obtained and visualized into 3 types of maps, namely network, overlay, and density. The conclusion from this literature study is that there are still limited publications related to the research topic of the role of university public relations in the presence of foreign students in Indonesia. By selecting a number of terms that are relevant but rarely appear, new research topics with a high level of novelty and large research gaps are obtained.